Influence of the Drive Plate with Different Surface Textures on the Property of Carbonyl Iron-Based Magnetorheological Fluid - He Lu; Lifeng Wang; Lili Dai; Hongxing Ding; Qiuxiang Zhang; Xinhua Liu (Advances in Materials Science and Engineering)
Aiming to study the effect of drive plate with different surface topographies on the wear property of magnetorheological fluid (MRF), some specific experiments are carried out and analyzed in this paper. Firstly, experiment materials and test methods for MRF are elaborated, and four different surface topography drive plates are designed and manufactured. MRF test-bed is built up to test the rheological properties of MRF. Moreover, the surface morphology of particles is taken using a scanning electron microscope (SEM). Finally, experimental results show that there are remarkable influences on tribological properties of carbonyl iron-based MRF with different drive plates. Therefore, the drive plate with specific surface topography can meet the needs of different MRF transmission systems.